The Immune System Drives Synapse Loss During Lipopolysaccharide-Induced Learning and Memory Impairment in Mice - Xin, Yi-Rong; Jiang, Jun-Xing; Hu, Yang; Pan, Jun-Ping; Mi, Xiang-Nan; Gao, Qin; Xiao, Fei; Zhang, Wei; Luo, Huan-Min (Frontiers in Aging Neuroscience, 2019)
Although lipopolysaccharides (LPS) have been used to establish animal models of memory loss akin to what is observed in Alzheimer’s disease (AD), the exact mechanisms involved have not been substantiated. In this study, we established an animal model of learning and memory impairment induced by LPS and explored the biological processes and pathways involved. Mice were continuously intraperitoneally injected with LPS for 7 days. Learning- and memory-related behavioral performance and the pathological processes involved were assessed using the Morris water maze test and immunostaining, respectively. We detected comprehensive expression of C1q, C3, microglia, and their regulatory cytokines in the hippocampus. After 7 days of LPS administration, we were able to observe LPS-induced learning and memory impairment in the mice, which was attributed to neural impairment and synapse loss in the hippocampus. We elucidated that the immune system was activated, with the classical complement pathway and microglial phagocytosis being involved in the synapse loss. This study demonstrates that an LPS-injected mouse can serve as an early memory impairment model for studies on anti-AD drugs.